Differences in playing characteristics between Lee Chong Wei and Lin Dan / Muhammad Afifuddin Mohd Azhar - Mohd Azhar, Muhammad Afifuddin (2017)
A study to analysed the different in playing characteristic between winning and losing among badminton players were lack and not clearly discussed in the previous literature. The purpose of this study was to identify the different in playing characteristics between Lee Chong Wei and Lin Dan. There were two players and they were split into four groups which were Lee Chong Wei winning and losing, and Lin Dan winning and losing. 20 world championship level matches had been taken to be analysed which was five winning matches and five losing matches each. The playing characteristics that had been analysed were rally, short serve, long serve, receive net, receive return, smash, net, unforced error net, unforced error out, return, outcome win, outcome lose, cause unforced error, cause smash, cause opponent, cause return, cause net, cause drop shot and cause serve. The result were determined by using One-way ANOV A where to analyse the different in playing characteristics between both players. The data shown that playing characteristics that had significant difference (p < 0. 05) between Lee Chong Wei and Lin Dan were rally (F = 13. 792, p < 0.000), short serve (F = 14.925, p < 0.000), receive net (F = 16.472, p < 0.000), receive return (F = 17.910, p < 0.000), smash ( F = 7. 711, p < 0.000), net (F = 5. 732, p < 0.001), unforced error net (F = 8.509, p < 0.000), unforced error out (F = 6.370, p < 0.000), return (F = 11.7 08, p < 0.000), outcome win (F = 20.591, p < 0.000), outcome lose (F = 19.093, p < 0.0 00), cause unforced error (F = 15.116, p < 0. 000) and caused opponent (F = 7.017,p < 0.000).